DAYA PENERIMAAN SISWA TERHADAP PENGGUNAAN QUIZIZZ SEBAGAI MEDIA EVALUASI BELAJAR DI SEKOLAH MENENGAH KEJURUAN - Nadya Nur Akmalia, - (2023)
In an era of advancing technology, it is essential for teachers to develop technological skills, adapt teaching methods, explore learning strategies, promote student collaboration, and be adaptable to technological developments. Teachers should create engaging, inclusive, and relevant learning environments in the increasingly digital world. Vocational and technological education play a vital role in meeting these needs and improving the quality of human resources. Platforms are learning evaluation media that can create more interactive and adaptive learning experiences. One of the platforms that researchers will investigate is Quizizz. The research aims to analyze students' acceptance of using Quizizz as an evaluation tool. The study adopts a quantitative explanatory approach through a survey, using purposive sampling to gather data from 72 students in vocational schools who used Quizizz in their learning process. The factors influencing students' acceptance of Quizizz are Perceived Playfulness, Perceived Usefulness, and Perceived Ease of Use. The research findings show that students positively accept the use of Quizizz as an evaluation medium. They view Quizizz as a fun and beneficial tool in the learning process. Factors like Perceived Playfulness, Perceived Usefulness, and Perceived Ease of Use significantly influence students' intention to use Quizizz. These findings have important implications for developing more effective and engaging learning technologies. Moreover, the research results can guide learning application developers in designing platforms that are attractive, user-friendly, and effective in improving student learning achievements..